Щодо відповідності концепцій реформування правоохоронної системи держави принципам національної безпеки України - Зозуля, І. В.; Zozulia, I. V.; Зозуля Ігор (Форум права. - 2008. - № 2. – С. 131-151, 2008)
Виконано аналіз відповідності принципам національної безпеки України окремих положень розроблених (чи таких, що розробляються) за Указами Президента України, концепцій реформування правоохоронних органів держави, зокрема, кримінальної юстиції України, системи органів Міністерства внутрішніх справ України, Служби безпеки України, Державної кримінально-виконавчої служби України, Державної прикордонної служби України на період до 2015 року.

The analysis of conformity to principles of national safety of Ukraine of separate positions developed (or developed) under Decrees of the President of Ukraine, of concepts for reforming of law enforcement bodies of the state, in particular, criminal justice of Ukraine, system of bodies of the Ministry of Internal Affairs of Ukraine, Security service of Ukraine, the State criminal-executive service of Ukraine, the State boundary service of Ukraine for the period till 2015 is executed.

Выполнен анализ соответствия принципам национальной безопасности Украины отдельных положений разработанных (или разрабатываемых) по Указам Президента Украины, концепций реформирования правоохранительных органов государства, в частности, криминальной юстиции Украины, системы органов Министерства внутренних дел Украины, Службы безопасности Украины, Государственной уголовно- исполнительной службы Украины, Государственной пограничной службы Украины на период до 2015 года.
About conformity of concepts for reforming of law-enforcement system of the state to principles of national safety of Ukraine
О соответствии концепций реформирования правоохранительной системы государства принципам национальной безопасности Украины
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; національна безпека; реформування; правоохоронні органи; национальная безопасность; реформирование; правоохранительные органы; national security; reforming; law enforcement agencies